Visualization of moral contents in a fairy tale - Рогожа, Марія Михайлівна (Київський національний університет імені Тараса Шевченка, 2019)
Contemporary culture is represented in the paper in the fairy tale optics in its ethical dimensions. Such prospects allow to ascertain ethical values which contemporaneity draws in archaic stratum of culture and generates basing on invariants of past. Using M. M. Bakhtin's ideas of great time of culture and outsideness, the author exposes a fairy tale as a phenomenon that once appeared in archaics but in every further cultural-historic period is able to represent its new facets what are unknown to all previous epochs. A fairy tale acts in therapeutic, orienting and educational functions since the time if its origins. Today a fairy tale has lost archaic horror tinge and obtained some romantic veil and moralistic color. These dimensions are reflected in an image of a hero. The paper points out the distinction between ethical and democratic heroes (the idea of M. E. Meletinsky). It is mentioned that content of an image of a democratic hero is better grasped by the N. Tec's concept a "dormant hero". It is a dormant hero whom contemporary culture comprehends most of all types of a fairy tale heroes. He leaves an impression that everybody can find oneself at his place. His heroic powers are ex- posed gradually. During the storytelling, it is turned out that he possesses definite virtues, personifies moral integrity. It is mentioned in the paper that today there are transformations in the comprehension what qualities are virtues. Qualities necessary for support of ancestors' cult as well as for keeping house were considered as virtues in archaic culture whereas contemporaneity represents in current fairy tale adaptations qualities clear for people today, such as valor, courage, resourcefulness, quick-wittedness. Virtues allow hero to negotiate obstacles, pass tests. Ethical pathos of a fairy tale is accumulated in victorious struggle against evil, for realization of justice, resumption of the lost equity. Ethical content of a fairy tale are visualized. At the basic level, visualization of good and evil is represented in immediate reality of beauty and ugliness. The second level of ethical content visualization is specified by imagination which allows audience to create images and visualize meanings in free flight of fancy. The third level is determined by proper ability of a fairy tale to use symbols. At that level, heroes are represented as symbols-keepers of cultural memory.

У статті сучасна культура (зокрема в етичних вимірах) представлена в оптиці чарівної казки, що дало змогу висвітлити етичні цінності, які сучасність черпає в архаїчних пластах культури й генерує, засновуючись на інваріантах минулого. Казка, з'явившись в архаїці, спроможна відкривати в кожну культурно-історичну добу нові свої грані, смисли, невідомі у часи виникнення. Визначено, що від свого виникнення до сьогодення чарівна казка виконує терапевтичну, орієнтуючу і виховну функції. У сучасній культурі казка втратила колорит архаїчного жаху й набула певного романтичного флеру і моралістичного забарвлення. Це знаходить відображення в образі героя. Для сучасної культури саме дрімаючий герой є найбільш прийнятним типом героя. Він залишає враження, що на його місці може опинитися кожен. Героїчне начало в ньому розкривається поступово. У ході оповідання виявляється, що він володіє певними чеснотами, втілює моральну цілісність. Ці якості дають йому змогу подолати перешкоди, пройти випробування. Етичний пафос чарівної казки полягає у переможній боротьбі із злом, втіленні/відновленні справедливості.
Візуалізація етичних змістів у чарівній казці
Keywords: чарівна казка; герой чарівної казки; чеснота; моральна цілісність; дрімаючий герой; чарівні сили; справедливість; візуалізація етичних змістів; fairy tale; fairy tale hero; virtue; moral integrity; dormant hero; magic forces; justice; visualization of ethical content